How Do We Motorically Resonate in Aging? A Compensatory Role of Prefrontal Cortex - Di Tella, Sonia; Blasi, Valeria; Cabinio, Monia; Bergsland, Niels; Buccino, Giovanni; Baglio, Francesca (Frontiers in Aging Neuroscience, 2021)
Aging is the major risk factor for chronic age-related neurological diseases such as neurodegenerative disorders and neurovascular injuries. Exploiting the multimodal nature of the Mirror Neuron System (MNS), in recent years rehabilitative interventions have been proposed based on motor-resonance mechanisms. Despite the considerable evidence of the MNS’ functionality in young adults, further investigation of the action-observation matching system is required in aging, where well-known structural and functional brain changes occur. Twenty-one healthy young adults (mean age 26.66y) and 19 healthy elderly subjects (mean age 71.47y) underwent a single MRI evaluation including a T1-3D high-resolution and functional MRI (fMRI) with mirror task. Morphological and functional BOLD data were derived from MRI images to highlight cortical activations associated with the task; to detect differences between the two groups (Young, Elderly) in the two MRI indexes (BOLD and thickness z-scores) using mixed factorial ANOVA (Group*Index analyses); and to investigate the presence of different cortical lateralization of the BOLD signal in the two groups. In the entire sample, the activation of a bilateral MNS fronto-parietal network was highlighted. The mixed ANOVA (pFDR-corr <.05) revealed significant interactions between BOLD signal and cortical thickness in left dorsal premotor cortex, right ventral premotor and prefrontal cortices. A different cortical lateralization of the BOLD signal in frontal lobe activity between groups was also found. Data herein reported suggest that age-related cortical thinning of the MNS is coupled with increased interhemispheric symmetry along with premotor and prefrontal cortex recruitment. These physiological changes of MNS resemble the aging of the motor and cognitive neural systems, suggesting specific but also common aging and compensatory mechanisms.